DESKRIPSI KEMAMPUAN BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL BANGUN DATAR PADA SISWA KELAS VIII SMP NEGERI 3 SUNGGUMINASA - Yusril Chikal Ashabulkahfi; Nursakiah (Jurnal Penalaran dan Riset Matematika, 2022)
The ability to think creatively can be seen from the process of solving problems in various ways. Student creativity in learning mathematics becomes a reference for students in solving mathematical problems using their own way of solving them. Information was obtained that students were less creative in the process of working on questions, students tended to get confused and tried to see answers from their friends compared to thinking for themselves what the answers to these questions were. This study aims to determine students' creative thinking skills in solving flat shape problems in class VIII students of SMP Negeri 3 Sungguminasa. This research is a descriptive study using qualitative research methods which will provide an overview of the creative thinking abilities experienced by students in solving flat shape problems in class VIII SMP Negeri 1 Sungguminasa. The data collection technique used was in the form of giving written tests and interviews. The indicators of creative thinking skills used in this study are fluency, flexibility, and novelty. Based on processed data, it was found that subjects with high abilities met all indicators of creative thinking ability, namely fluency, flexibility and novelty. Subjects with moderate abilities were only able to fulfill two indicators of creative thinking ability, namely fluency and flexibility. Subjects with low abilities were only able to meet one indicator of creative thinking ability, namely fluency.